1999
DOI: 10.1021/jp9907692
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Elevation of Freezing Temperature of CCl4 in Graphitic Micropores

Abstract: The freezing behavior of CCl 4 confined in graphitic micropores of activated carbon fibers (ACFs) was examined by use of differential scanning calorimetry over the temperature range of 180 to 320 K. For ACF of average pore width, w ) 1.1 nm, we observed a clear peak showing that the freezing temperature is 299 K. The freezing temperature was elevated by 57 K. However, the enthalpy of freezing was only 1.0% of that of the bulk liquid CCl 4 to an fcc solid phase. CCl 4 confined in micropores of w ) 0.80 nm had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 20 publications
5
56
0
Order By: Relevance
“…Miyahara and Gubbins [113] have suggested that when interaction potential energy of a molecule with the pore wall is grater than that with the pore wall consisting of adsorbate molecules, the melting temperature should be elevated with decreasing pore width and the melting process disappears in micropores. Kaneko and co-workers [114][115][116] showed, with the aid of in situ X-ray diffraction, that for some adsorbates (for example, CCl 4 molecules) confined in graphitic micropores form a molecular assembly having a more long-range order than the bulk liquid. Summing up, if the graphite micropores were considered, an anomaly of phase transition even for small molecules should be observed.…”
Section: Calorimetric Datamentioning
confidence: 99%
“…Miyahara and Gubbins [113] have suggested that when interaction potential energy of a molecule with the pore wall is grater than that with the pore wall consisting of adsorbate molecules, the melting temperature should be elevated with decreasing pore width and the melting process disappears in micropores. Kaneko and co-workers [114][115][116] showed, with the aid of in situ X-ray diffraction, that for some adsorbates (for example, CCl 4 molecules) confined in graphitic micropores form a molecular assembly having a more long-range order than the bulk liquid. Summing up, if the graphite micropores were considered, an anomaly of phase transition even for small molecules should be observed.…”
Section: Calorimetric Datamentioning
confidence: 99%
“…In particular, fluids confined in restricted geometries, provide many intriguing behaviors examples. For example, experiments performed on some porous materials show a melting point elevation in narrow pores [1][2][3][4], in contrast to the almost universally observed depression of transition temperatures in larger pores. Additionally, in nano-metric pores, the adsorbed phase is always heterogeneous; the layers differing in their distance from the pore wall have different properties.…”
Section: Introductionmentioning
confidence: 99%
“…23 Similar elevation was observed for CCl 4 , which was supported by a free energy calculation. 24,25 Recently, this phase transition anomaly was evidenced by vibrationrotation spectroscopy at low temperature for CH 4 in the pores of SWCNH. 26 CH 4 is the main component of natural gas.…”
Section: In-pore Phase Anomalymentioning
confidence: 95%